1997
DOI: 10.1103/physrevd.56.6081
|View full text |Cite
|
Sign up to set email alerts
|

Search for gravitational radiation from Supernova 1993J

Abstract: The results of a coincidence search for a short burst of gravitational radiation from supernova 1993J with the Allegro and Explorer cryogenic resonant-mass detectors are reported. No detection can be claimed, but an upper limit on the possible strain amplitude from the supernova is calculated. A new method of performing coincidence searches is introduced. ͓S0556-2821͑97͒00322-6͔PACS number͑s͒: 04.80.Nn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…From these data we generated histograms which show the number of events as a function of voltage squared. Once V 2 ∝ T figure 6 shows how it fits with a thermal distribution [18]…”
Section: Some Results From Data Analysismentioning
confidence: 99%
“…From these data we generated histograms which show the number of events as a function of voltage squared. Once V 2 ∝ T figure 6 shows how it fits with a thermal distribution [18]…”
Section: Some Results From Data Analysismentioning
confidence: 99%
“…Analysis of data recorded by Geograv for SN1987A (Amaldi et al 1987) and by Explorer-Allegro for SN1993J (Mauceli et al 1997), showed that there are GW candidate events, which the authors themselves do not consider as real signals because the GW energy calculated for a standard pulse with a duration τ g = 1 ms (and hence bandwidth 1 kHz) gives E gw ≈ 10 3 M c 2 for both supernovae. However, in the case of pulse duration of about 1 s (and hence bandwidth 1 Hz) the GW energy needed for producing the same GW amplitude is about 1 M c 2 .…”
Section: Discussionmentioning
confidence: 99%